The Effect of Work Discipline and Organizational Culture on Motivation and its Impact on Employee Performance in Water Tourism in Muara Enim Regency - Putra, Ade; Asiati, Diah Isnaini; Trihandayani, Zaleha (International Journal of Business, Management and Economics, 2022)
This study aims to determine the effect of work discipline and organizational culture on motivation and its impact on employee performance in water tourism in Muara Enim Regency. This type of research is Associative. The sample in this study was employees at water tourism in Muara Enim Regency, totalling 87 people who were selected using a proportionate random sampling technique. The data used in this study are primary data with questionnaire data collection methods. The data analysis technique used is Structural Modeling Equation (SEM) with Program Applications. The results showed that: (1) Work discipline positively and significantly influenced employee motivation at Water Tourism, Muara Enim Regency. (2) There is a positive and significant influence of organizational culture on employee motivation in Muara Enim Regency Water Tourism. (3) Work discipline has a positive and significant effect on employee performance at Water Tourism, Muara Enim Regency. (4) There is a negative and insignificant influence between organizational culture on employee performance at Water Tourism, Muara Enim Regency. (5) Motivation has a positive and significant influence on employee performance at Water Tourism in Muara Enim Regency. (6) Motivation strengthens the influence of discipline on employee performance in Water Tourism, Muara Enim Regency. (7) Motivation strengthens the influence of organizational culture on employee performance at Water Tourism, Muara Enim Regency.